Vanishing Half - Bennett, Brit (New York Riverhead Books, 2020)
"The Vignes twin sisters will always be identical. But after growing up together in a small, southern black community and running away at age sixteen, it's not just the shape of their daily lives that is different as adults, it's everything: their families, their communities, their racial identities. Ten years later, one sister lives with her black daughter in the same southern town she once tried to escape. The other secretly passes for white, and her white husband knows nothing of her past. Still, even separated by so many miles and just as many lies, the fates of the twins remain intertwined. What will happen to the next generation, when their own daughters' storylines intersect? Weaving together multiple strands and generations of this family, from the Deep South to California, from the 1950s to the 1990s, Brit Bennett produces a story that is at once a riveting, emotional family story and a brilliant exploration of the American history of passing."--Provided by publisher.
108102
Keywords: 1900-1999; Twins -- Fiction; Sisters -- Fiction; African American women -- Fiction; Identity (Philosophical concept) -- Fiction; Coming of Age; Literary; Women; United States -- History -- 20th century -- Fiction; Historical fiction; Domestic fiction; Detective and mystery fiction; Fiction; History